Application and Efficacy Analysis of Genetically Engineered Heavy Metal-Resistant Strains in the Remediation of Cadmium-Contaminated Soil - Liu, Jiazhen; Zhu, Ziyu; Peng, Siwen; Ji, Xionghui; Xie, Yunhe; Wu, Jiamei; Lu, Yaoxiong; Fang, Ping (International Journal of Natural Resources and Environmental Studies, 2026)
This study evaluated the efficacy of genetically engineered Streptomyces strain PSQ for remediating cadmium (Cd)-contaminated mine soils in Hunan Province, where agricultural soils exhibit elevated Cd levels. A pot experiment was conducted with three treatments: blank control (CK), wild-type Streptomyces strain FQ1, and engineered strain PSQ. Soil physicochemical properties, plant heavy metal uptake, and microbial community dynamics were systematically assessed. Results showed that PSQ altered soil pH and redox potential, thereby influencing Cd mobility. Leachate Cd concentration was significantly higher in the PSQ treatment (2.325 mg/L) than in CK (1.89 mg/L), reflecting increased Cd solubility via microbial metabolism. However, bioavailable Cd decreased by 15.8% in PSQ-treated soil (mean 0.16 mg/kg) compared to CK (0.19 mg/kg), indicating effective Cd immobilization through complexation, reduction, and adsorption mechanisms. Plant uptake was enhanced in the PSQ group, with higher mean bioconcentration factors (BCF) for Cd relative to CK and FQ1 treatments. Notably, Amaranthus tricolor and Cyperus iria displayed strong Cd accumulation (BCF > 7), suggesting improved phytoextraction efficiency promoted by the engineered strain. The Alpha diversity of PSQ and FQ1 groups was lower than that of the CK group, but the intra-group differences were significant. The key microbial community was Saccharibacillus. Overall, strain PSQ reduced bioavailable Cd, augmented plant Cd enrichment, and modulated rhizosphere microbial communities, establishing a synergistic system involving exogenous engineered bacteria, indigenous microbiota, and plants. These findings provide a theoretical basis for bioremediation of Cd-contaminated soils.